Comparative study for seed layer solvent effects on structural and optical properties of MgZnO thin films deposited by chemical bath deposition technique - Faran Baig; Ali Asif; Muhammad Waseem Ashraf; Muhammad Imran (Materials Research Express, 2020)
C -axis oriented Magnesium doped Zinc Oxide (MgZnO) thin films are promising candidates for variety of applications especially optoelectronic devices. In this work, the effects of seeding solvents on structural and optical properties of MgZnO films were analyzed. The comparison was performed by varying the seed layer solvent i.e. 2-Methoxyethanol, 2-Propanol, Ethanol and Methanol. MgZnO thin films were synthesized on different seed layered glass substrates using Chemical Bath Deposition (CBD) method. The XRD results revealed the hexagonal wurtzite structure for all samples. However, the film with seed layer 2-Methoxyethanol solvent had preferred c -axis orientation and better crystallanity. For 2-Methoxyethanol solvent based seed layer: the morphological study showed wrinkled free, unfractured and highly aligned MgZnO nanorods grown perpendicular to the substrate. Energy dispersive x-ray (EDS) spectroscopy confirmed the presence of magnesium in ZnO film. Highest average transmittance of $80 % $ and band gap value of $3.3\,{\rm{eV}}$ was recorded through UV–vis spectroscopy. The optical constants (refractive index and extinction coefficient) were determined by reflectance and absorbance data. Furthermore complex dielectric constant and energy loss functions were estimated.